Multiplexed detection of eight respiratory viruses based on nanozyme colorimetric microfluidic immunoassay - Wu, Feng; Cai, Defeng; Shi, Xueying; Li, Ping; Ma, Lan (Frontiers in Bioengineering and Biotechnology, 2024)
The ongoing pandemic of respiratory viruses such as SARS-CoV-1/2, influenza virus and respiratory syncytial virus caused serious damage to human and large number of deaths. The detection of respiratory viruses in infection early stage would be contributed to controlling the disease and preventing viral spread. However, the diversity of respiratory virus species and subtypes, their rapid antigenic mutations, and the limited virus release in early infection made the viral detection challenged. Herein, we reported a multiplexed microfluidic immunoassay chip for simultaneous detection of 8 respiratory viruses that with noticeable infection population, including influenza A, influenza B, respiratory syncytial virus, SARS-CoV-2, human bocavirus, human metapneumovirus, adenovirus, and human parainfluenza viruses. We optimized the nanomaterial of nanozyme (Au@Pt NPs) to improve labeling efficiency and significantly enhanced the detection sensitivity. We applied the nanozyme-binding antibodies to detect viral proteins with LOD of 0.1 pg/mL by naked-eye and microplate reader, only within 40 minutes. Furthermore, we screened specific antibodies against conserved proteins of each virus for the immunoassay, and the detection of clinical samples showed high specificity without cross-reactivity among the 8 pathogens. In addition, the microfluidic chip immunoassay showed high accuracy compared with RT-PCR assay in clinical sample detection with 97.2%/ 94.3% of positive/ negative coincidence rates. Together, our study provided a convenient, rapid and sensitive method for simultaneous detection of 8 respiratory viruses, which was meaningful for the early diagnosis of viral infection.Significantly, it could be widely used for the detection of pathogens and biomarkers only by replacing antigen-specific antibodies.